Mammals and fire in mediterranean ecosystems Ecological responses from the shrew Crocidura russula (Insectivora Soricidae) and the rodent Eliomys quercinus (Gliridae) in burned cork oak forest - Fons, R; Grabulosa, I; Marchand, B; Miquel, J; Feliu, C; Mas-Coma, S (VIE ET MILIEU-LIFE AND ENVIRONMENT, 1996)
Mammals and fire in mediterranean ecosystems. Ecological responses from the shrew Crocidura russula (Insectivora - Soricidae) and the rodent Eliomys quercinus (Gliridae) in burned crock oak forest. In the present work we report the ecological responses of two small mammals to fire. During a six-year post-fire period, both species were studied by the capture-mark-recapture on a 9 ha quadrate established in a recently burned cork oak forest. The white-toothed-shrew, Crocidura russula, was the least resistant species to fire, disappearing completely during the first two years. Reappearing on the third year, the population maintained a low effective with the same fluctuation similar to that observed within the control. Although faster than on other studied mediterranean ecosystems, its allochthonous ristablishment on the burned cork oak forest, seems to be dependent on the litter reconstitution. Due to its rupicolous habits, its biotope specialization, highly favored by the presence of rocks on the capture quadrate, and some physiological apects (hibernation), the dormouse Eliomys quercinus, showed a better pre-adaptive response to the post-fire stress. The survival of a nucleus of autochtonous individuals insured, from the first year, a slow, but progressive recovery of the population.
Keywords: Cork Oak Forest; Crocidura russula; ELIOMYS QUERCINUS; fire; mammals